Editorial: Volume 2 | Issue 1 | July 2022 (Culturas Científicas, 2021)
Editorial written by the Director of the Magazine, Dr. Wilfredo Quezada Pulido, for the Volume 2 | Issue 1 published on July 31, 2021.